Phase transitions and critical phenomena - Domb, Cyril; Lebowitz, Joel Louis, 1930-; Green, Melville S. (Acad. Press, 2001)
The field of phase transitions and critical phenomena continues to be active in research, producing a steady stream of interesting and fruitful results. No longer an area of specialist interest, it has acquired a central focus in condensed matter studies. The major aim of this serial is to provide review articles that can serve as standard references for research workers in the field, and for graduate students and others wishing to obtain reliable information on important recent developments. The two review articles in this volume complement each other in a remarkable way. Both deal with what might be called the modern geometric approach to the properties of macroscopic systems. The first article by Georgii (et al.) describes how recent advances in the application of geometric ideas leads to a better understanding of pure phases and phase transitions in equilibrium systems. The second article by Alava (et al.) deals with geometrical aspects of multi-body systems in a hands-on way, going beyond abstract theory to obtain practical answers. The combination of computers and geometrical ideas described in this volume will doubtless play a major role in the development of statistical mechanics in the twenty-first century.